The Construction of Sense of Place: Observations from the Field. Issue 1 (2nd January 2017) - Jennings, Steve
Abstract : An introspective look at the illustrative power of field experience, this article makes analogies between field experiences and the larger pursuit of geography research. The setting is the White Mountains of California, but the ideas in this article expand the local experience that informs much larger themes.